Fabrication of high energy and high power density supercapacitor based on MnCo2O4 nanomaterial. (October 2019) - Shanmugavadivel, M.; Dhayabaran, V. Violet; Subramanian, M.
Abstract: The supercapacitor electrode material MnCo2 O4 was successfully prepared by a facile solution combustion method. XRD, FT-IR, UV-DRS, SEM and TEM instruments were employed to study the physico-chemical and surface properties of the MnCo2 O4 . The electrochemical performance of the MnCo2 O4 electrode was evaluated by cyclic voltammetry and galvanostatic charge-discharge studies. The modified electrode shows an excellent cyclic behaviour with a wide potential window of −1.2 to 1.5V. The highest specific capacitance value of MnCo2 O4 at the scan rate of 10 mVs −1 was 270 Fg -1 and it shows the enhanced capacitive character of the electrode material. The measured capacitance fading after 1000 cycles was only about 7.6% and this shows the excellent cyclic stability of the material. The maximum energy and power density calculated from the constant charge-discharge cycles were 14.85 Wkg -1 and 495 Whkg −1 respectively. The electrochemistry of MnCo2 O4 proves that it can be used as a high energy and power density electrode material for high performance supercapacitors. Graphical abstract: Image 1 Highlights: MnCo2 O4 nanomaterial was prepared by solution combustion method. The MnCo2 O4 electrode shows the maximum specific capacitance of 270 Fg -1 at the scan rate of 10 mVs 1 . The measured energy density and power density values (14.85 Wkg -1 and 495 Whkg −1 ) shows the outstanding electrochemical power characteristics of the MnCo2 O4 electrode material.